THEORY ON THE EXPERIMENTAL DATA FOR THE MOMENTUM PROTON DISTIBUTIONS IN 7 6 Li He + p CHANNEL - Afanas’eva, N. V.; Burkova, N. A.; Zhaksybekova К. А.; Safiulin, D. R. (Recent Contributions to Physics, 2009)
Within the nn -model for the ground state of 6 + He(0 ,1) nuclei and first excited one 2 + , 1 the proton momentum distributions have been calculated in 7 6 Li He+p fragmentation channel. A comparison with available theoretic calculations as well experimental data on the process 7 6 Li(e,e p) He is given.